RANCANG BANGUN SISTEM INFORMASI PENDATAAN SAPI PADA ARDIAN PERKASA FARM BERBASIS WEBSITE - Amalia Ayu Ardian (2022)
Ardian Perkasa Farm is a business sector in the livestock sector that carries out maintenance and fattening of cattle, the output produced is in the form of quality livestock products. Livestock products will continue to increase along with population and public consumption. Therefore, it is necessary to increase the livestock activists (breeders). In improving livestock activists (breeders), Ardian Perkasa Farm has developed a development using a noise system. In the noise system, Ardian Perkasa Farm has difficulty recording incoming and outgoing data after the cooperation agreement. The incoming data is in the form of cattle data, farmer data, and outgoing data (sales data). In the data collection, the manager must go to the farmer's house to collect data, then must first write it manually in a book, then enter it into a software, namely Microsoft Excel. However, with a lot of data that can make the previous files mixed up and hamper the performance of the website manager. The data collection for cattle at Ardian Perkasa Farm uses the waterfall research method. The results of this study are a website-based cattle data collection information system that was built as a media to assist in data collection of cattle at Ardian Perkasa Farm. This website is divided into three based on the authority of the First party as the Owner or the Investor has the authority based on information on the production and development of the capital that has been maintained for the breeder. Second, as Livestock Activator or Peter or Paddy who has the authority to run the production that has been carried out, and the Third Party as Livestock Manager or Admin which has the authority to maintain the relationship between the First Party and the Second Party, as well as livestock production and business stability, as well as providing solutions and socialization to the line of business. The website is safer in data storage and easier to access, with this website it is hoped that it can help the performance of livestock managers at Ardian Perkasa Farm, Gunung Kidul district.